Особливості периферичного кровообігу у чоловіків, зайнятих у промисловому виробництві - Пшибельський, Володимир; Шевчук, Тетяна; Киричук, Олена; Pshibelskiy, Vladimir; Shevchuk, Tatiana; Kirichuk, Aliona (Східноєвропейський національний університет імені Лесі Українки, 2014)
Вивчено особливості кровообігу верхніх та нижніх кінцівок в осіб чоловічої статі, які зайняті у промисловому виробництві. Виявлено достовірно відмінні нижчі значення показників периферичної гемодинаміки верхніх та нижніх кінцівок у чоловіків, які працюють на виробництві, порівняно з контрольною групою. Спостерігається тенденція до зниження кровообігу ведучої кінцівки у чоловіків контрольної та експериментальної групи. The last decade has increased the incidence and prevalence of diseases of the upper and lower limbs of persons employed in the industrial production. According to the literature, the position ekobiologichesky environment significantly affects the health, quality and length of human life. Adverse factors affect physiological state of the human body as a whole, therefore, assessment of the impact of urbanization on the hemodynamic dysfunction is very urgent for scientists and physicians. These data strongly suggest the feasibility and relevance of the study of the influence of industrial value to the peripheral circulation in males of mature age. The aim of our study was to investigate the features of peripheral blood circulation in males who are exposed to industrial pollution. To investigate the peripheral circulation technique was used rheovasography. Analysis of the results showed a significant difference valuesof the indicators reovazogrammy forearm between the first and the second group of subjects. Persons employed in industrial production was found significantly lower values of the time delay reovolnyrheogram forearm right and left sides, and both sides rheographic index compared with those ecologically clean zone. According to figures reovazogramy shin was a significant difference between the values of the index rheographic index on both sides in the test, but the test of the first group of this indicator were lower. Also observed low values of measured time delays and reovolnyrheographic coefficient left side of the drumstick men working in manufacturing. The asymmetry coefficient reovazogramy forearm and shin percentage was significantly higher in the first group of subjects, equally with the control.
Features of Peripheral Blood Circulation in Men Employed in the Industrial Production
Keywords: промисловість; реограма гомілки; реограма передпліччя; периферичний кровообіг; industry; rheogram shin; rheogram forearm; peripheral circulation